2010
DOI: 10.1128/jb.00534-10
|View full text |Cite
|
Sign up to set email alerts
|

Small Genes under Sporulation Control in the Bacillus subtilis genome

Abstract: Using an oligonucleotide microarray, we searched for previously unrecognized transcription units in intergenic regions in the genome of Bacillus subtilis, with an emphasis on identifying small genes activated during spore formation. Nineteen transcription units were identified, 11 of which were shown to depend on one or more sporulation-regulatory proteins for their expression. A high proportion of the transcription units contained small, functional open reading frames (ORFs). One such newly identified ORF is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 44 publications
0
65
0
Order By: Relevance
“…To this end, we fused the target promoters of the BceRS system (P bceA ), of the PsdRS system (P psdA ), and selected target promoters of s M , s X and s W (P ydaH , P sigX and P pspA , respectively), and one promoter which is regulated by all three s factors, P bcrC , to a promoter-less luxABCDE reporter (Radeck et al, 2013;Schmalisch et al, 2010). The resulting promoter-lux fusions were integrated into the chromosome of B. subtilis W168 WT cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, we fused the target promoters of the BceRS system (P bceA ), of the PsdRS system (P psdA ), and selected target promoters of s M , s X and s W (P ydaH , P sigX and P pspA , respectively), and one promoter which is regulated by all three s factors, P bcrC , to a promoter-less luxABCDE reporter (Radeck et al, 2013;Schmalisch et al, 2010). The resulting promoter-lux fusions were integrated into the chromosome of B. subtilis W168 WT cells.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional promoter fusions to bacterial luciferase (luxABCDE) were constructed in pAH328 (Schmalisch et al, 2010) or the pAH328 derivative pBS3Clux (Radeck et al, 2013) using NotI/SalI or EcoRI/SpeI restriction enzymes, respectively. All strains used in this study are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…RnaC/S1022 was first identified in a microarray screen of B. subtilis intergenic regions, and its expression was found to be completely dependent on the sigma factor SigD during the exponential growth phase on LB medium (24,109). Recently, RnaC/S1022 was shown to modulate the cellular levels of the important transcriptional regulator AbrB via a direct sRNA-mRNA interaction (24).…”
Section: Independently Expressed Small Rnas and Rna Antitoxinsmentioning
confidence: 99%
“…9) ytrH was found to be a novel sporulation gene involved in cortex formation and stability. 13) Schmalisch et al 14) reported that six paralogous genes were newly identified small proteins under sporulation control. Mutants of these genes had no significant deleterious effects on the production of heat-resistant spores, but a multiple mutant lacking six paralogous genes showed sporulation efficiency slightly higher than the wild type.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Several genes for small ORFs that are transcribed in response to sporulation have provided new biological insights. 9,[13][14][15] A 40-amino-acid peptide, MciZ, acts to block Z-ring formation during sporulation by inhibiting the polymerization of FtsZ in the mother cell. 9) ytrH was found to be a novel sporulation gene involved in cortex formation and stability.…”
mentioning
confidence: 99%